Application of the Job Demands-Resources Model to Understand the Mechanism of Job Rotation as a Predictor of Innovative Work Behavior - Fauzan Akbar; Reni Rosari (LP2M IAIN Palopo, 2026)
Based on the Job Demands-Resources model (Bakker & Demerouti, 2007), we conducted an empirical study on how job rotation mechanisms in the form of Employee-Initiated Job Rotation (IRO), Management-Decision-Based Job Rotation (MRO), and No Job Rotation (TRP) impact work attitudes in the form of work engagement, job tension, job satisfaction, organizational commitment, and innovative work behavior. Data collection was conducted through an online survey distributed via Microsoft Form to employees at the Ministry of Finance. There were 1,151 questionnaires analyzed using Structural Equation Modeling (SEM) to test the research hypotheses. The results of this study indicate that job engagement, job satisfaction, and organizational commitment sequentially positively mediate the influence of IRO and IRO on innovative work behavior. At the same time, job tension, job satisfaction, and organizational commitment sequentially negatively mediate the influence of TRP on innovative work behavior.